PUBLIC UNDERSTANDING OF THE USE OF FINTECH INVESTMENT APPLICATIONS INDODAX QUALITATIVE STUDY ON BEGINNER USERS - Depita Permata Sari; M. Lutfi Ramdoni; Muhammad Fauzan (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2025)
The development of financial technology (fintech) in Indonesia is encouraging presence Various digital investment platforms, including Indodax, are popular as a crypto asset trading app. Ease of access and potential profits attract novice users, but this is not always accompanied by an adequate understanding of app usage, crypto investment concepts, and risks and security. This study aims to determine novice users' understanding of the Indodax app. The study used a qualitative approach through in-depth interviews with informants selected using purposive sampling and analyzed using thematic analysis. The results indicate that novice users' understanding is still limited to basic transaction functions, while their understanding of advanced features, investment risks, and digital security remains low. This understanding is influenced by digital financial literacy, information sources, and perceived ease of use of the app, with the majority of users relying on social media rather than official sources. The study concludes that improving digital financial literacy and targeted education are essential for novice users to use fintech investment apps wisely and safely.